Philosophical cosmology and religious polemic: The "worship of creation" in the writings of Philo of Alexandria and the Wisdom of Solomon. (September 2021) - Wasserman, Emma
This article treats Hellenistic Jewish literature that ridicules the alleged worship of the elements, the heavens, the heavenly bodies, or other "parts" of the cosmos, especially as developed in the writings of Philo of Alexandria and Ps-Solomon. It is argued that such claims constitute a distinctive sub-type of religious polemic that draws on and adapts from Platonic and Stoic traditions of cosmology. Such polemics are most clearly developed in Philo's treatises and in chapter 13 of the Wisdom of Solomon, but they also appear in more abbreviated form in the fragments of Philo of Byblos and Aristobulus. I suggest that these traditions of invective may bear on the interpretation of Rom 1:19–23, but only in an indirect way.